2004
DOI: 10.1046/j.8755-8920.2003.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of the Growth Hormone in Human Endometrium and Decidua

Abstract: The glandular cells of the human endometrium express GH from the late luteal phase throughout pregnancy in the decidual tissue. We suppose that GH plays an important role in blastocyst implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
0
26
0
4
Order By: Relevance
“…In this regard it is interesting that uterine endometrium displays altered telomerase activity in a menstrual cycle-dependent manner despite its somatic origin (41). hGH has also been detected in endometrial epithelial cells (39). Thus, it may be possible that autocrine hGH participates in the regulation of telomerase activity required for temporal specific or cyclical proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard it is interesting that uterine endometrium displays altered telomerase activity in a menstrual cycle-dependent manner despite its somatic origin (41). hGH has also been detected in endometrial epithelial cells (39). Thus, it may be possible that autocrine hGH participates in the regulation of telomerase activity required for temporal specific or cyclical proliferative activity.…”
Section: Discussionmentioning
confidence: 99%
“…GHR and GHR mRNA are also present in the uterus, including glandular and stromal cells [111][112][113], the decidua [114], and myometrium [111]. It is therefore possible that GH may act in an autocrine or paracrine way to regulate uterine growth or function.…”
Section: Uterine Tissuementioning
confidence: 99%
“…hGH is also synthesized and functions locally within extrapituitary sites such as the mammary gland and endometrium (5). hGH is reported to be synthesized in the endometrial luminal epithelial cells during the mid to late luteal phase of the menstrual cycle (6). Slater et al (7) reported the increased expression of hGH in the endometrial epithelium-derived cells in both endometriosis and endometrioid adenocarcinoma.…”
mentioning
confidence: 99%